Analysis on the operation parameters of cooling water system in 45.22T hybrid magnet experiment. (April 2023) - Zhou, Chenfei; Tang, Jiali
Abstract: Chinese Steady High Magnetic Field Facility produced a steady field of 45.22 T by its hybrid magnet, which was the highest steady magnetic field in the world. The cooling water system was used to maintain the cool temperature environment for the insert resistive magnet coils and it was completed the upgrading in the year 2020 after ensuring the 40 T hybrid magnet experiment. The performance parameters and characteristics of the transformed cooling water system has been introduced. The variation trend of the magnet circulating water flow rate and the deionized water quality in 45.22 T hybrid magnet experiment has been analyzed, and also the heat exchange effect between the primary chilled water circuits and the secondary deionized water circuits were calculated. Some problems in cooling water system operation in this time hybrid magnet experiment have been pointed out.